2014
DOI: 10.3892/mmr.2014.2485
|View full text |Cite
|
Sign up to set email alerts
|

Desmocollin-2 affects the adhesive strength and cytoskeletal arrangement in esophageal squamous cell carcinoma cells

Abstract: Desmocollin-2 (DSC2), a transmembrane glycoprotein belonging to the desmosomal cadherin family, has been found to be differentially expressed in several types of cancer and to be involved in tumor progression. The tumor metastasis suppressing property of DSC2 in esophageal squamous cell carcinoma (ESCC) has been described, however, its contribution to cell cohesion in ESCC remains to be elucidated. In the present study, using RNA interference (RNAi), the expression of DSC2 was silenced in SHEEC and KYSE510 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…DSC2 was found to decrease in acantholytic squamous cell carcinoma of the skin (Jurčić et al, 2015). Several studies by the Wang-Kai Fang team discovered that downregulated desmocollin-2 reduces cell-cell adhesion, promotes cell aggressiveness by redistributing adherens junctions, and activating β-catenin signaling in esophageal squamous cell carcinoma (Fang et al, 2013(Fang et al, , 2014. In addition, DSC2 is involved in the transformation, and development of esophageal tumors and DSC2 expression level and intracellular localization may serve as a predictor of patient outcomes (Fang et al, 2010).…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…DSC2 was found to decrease in acantholytic squamous cell carcinoma of the skin (Jurčić et al, 2015). Several studies by the Wang-Kai Fang team discovered that downregulated desmocollin-2 reduces cell-cell adhesion, promotes cell aggressiveness by redistributing adherens junctions, and activating β-catenin signaling in esophageal squamous cell carcinoma (Fang et al, 2013(Fang et al, , 2014. In addition, DSC2 is involved in the transformation, and development of esophageal tumors and DSC2 expression level and intracellular localization may serve as a predictor of patient outcomes (Fang et al, 2010).…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…Interestingly, using a DM-Dsg 2 TS, it was reported that Dsg2 supports mechanical tension in MDCK resting cells and during cardiomyocyte contraction ( Baddam, Arsenovic et al , 2018 ). In addition, Dsc2 KD in esophageal squamous carcinoma cell lines resulted in impaired intercellular adhesion and retraction of keratin-IFs ( Fang et al , 2014 ). Furthermore, DP I/II has been reported to support tension force across intercellular junctions when external stress was applied ( Price, Cost et al , 2018 ) and by cross-linking IFs to desmosomal cadherins ( Broussard, Yang et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…PKP2 may excite Top ash activity, leading to the translocation of desmosomes [33] . Another study has revealed that PKP2 can promote actin recombination and regulate the assembly of the desmosomal complex by connecting Ras homolog A and protein kinase C-dependent pathways [45] . In our study, the mRNA and protein levels of PKP2 were signi cantly upregulated in esophageal adenocarcinoma tissues compared with tissues of normal esophagus and esophagitis in rats.…”
Section: Discussionmentioning
confidence: 99%